Quantum dots as targeted doxorubicin drug delivery nanosystems - Monika Ruzycka-Ayoush; Patrycja Kowalik; Agata Kowalczyk; Piotr Bujak; Anna M. Nowicka; Maria Wojewodzka; Marcin Kruszewski; Ireneusz P. Grudzinski (Cancer nanotechnology, 2021)
Abstract Background Lung cancer is one of the most frequently diagnosed cancers all over the world and is also one of the leading causes of cancer-related mortality. The main treatment option for small cell lung cancer, conventional chemotherapy, is characterized by a lack of specificity, resulting in severe adverse effects. Therefore, this study aimed at developing a new targeted drug delivery (TDD) system based on Ag–In–Zn–S quantum dots (QDs). For this purpose, the QD nanocrystals were modified with 11-mercaptoundecanoic acid (MUA), L-cysteine, and lipoic acid decorated with folic acid (FA) and used as a novel TDD system for targeting doxorubicin (DOX) to folate receptors (FARs) on adenocarcinomic human alveolar basal epithelial cells (A549). NIH/3T3 cells were used as FAR-negative controls. Comprehensive physicochemical, cytotoxicity, and genotoxicity studies were performed to characterize the developed novel TDDs. Results Fourier transformation infrared spectroscopy, dynamic light scattering, and fluorescence quenching confirmed the successful attachment of FA to the QD nanocrystals and of DOX to the QD–FA nanocarriers. UV–Vis analysis helped in determining the amount of FA and DOX covalently anchored to the surface of the QD nanocrystals. Biological screening revealed that the QD–FA–DOX nanoconjugates had higher cytotoxicity in comparison to the other forms of synthesized QD samples, suggesting the cytotoxic effect of DOX liberated from the QD constructs. Contrary to the QD–MUA–FA–DOX nanoconjugates which occurred to be the most cytotoxic against A549 cells among others, no such effect was observed for NIH/3T3 cells, confirming FARs as molecular targets. In vitro scratch assay also revealed significant inhibition of A549 cell migration after treatment with QD–MUA–FA–DOX. The performed studies evidenced that at IC 50 all the nanoconjugates induced significantly more DNA breaks than that observed in nontreated cells. Overall, the QD–MUA–FA–DOX nanoconjugates showed the greatest cytotoxicity and genotoxicity, while significantly inhibiting the migratory potential of A549 cells. Conclusion QD–MUA–FA–DOX nanoconjugates can thus be considered as a potential drug delivery system for the effective treatment of adenocarcinomic human alveolar basal epithelial cells.